HIV Vaccine Development at a Crossroads: New B and T Cell Approaches - Ramesh Govindan; Kathryn E. Stephenson (Vaccines, 2024)
Despite rigorous scientific efforts over the forty years since the onset of the global HIV pandemic, a safe and effective HIV-1 vaccine remains elusive. The challenges of HIV vaccine development have proven immense, in large part due to the tremendous sequence diversity of HIV and its ability to escape from antiviral adaptive immune responses. In recent years, several phase 3 efficacy trials have been conducted, testing a similar hypothesis, e.g., that non-neutralizing antibodies and classical cellular immune responses could prevent HIV-1 acquisition. These studies were not successful. As a result, the field has now pivoted to bold novel approaches, including sequential immunization strategies to drive the generation of broadly neutralizing antibodies and human CMV-vectored vaccines to elicit MHC-E-restricted CD8+ T cell responses. Many of these vaccine candidates are now in phase 1 trials, with early promising results.